Quantitative analysis of F‐actin redistribution in astrocytoma cells treated with candidate pharmaceuticals. Issue 6 (11th February 2014) - Lockett, Stephen; Verma, Chrissie; Brafman, Alla; Gudla, Prabhakar; Nandy, Kaustav; Mimaki, Yoshihiro; Fuchs, Philip L.; Jaja, Joseph; Reilly, Karlyne M.; Beutler, John; Turbyville, Thomas J.; Vereb, György
Abstract Actin fibers (F‐actin) control the shape and internal organization of cells, and generate force. It has been long appreciated that these functions are tightly coupled, and in some cases drive cell behavior and cell fate. The distribution and dynamics of F‐actin is different in cancer versus normal cells and in response to small molecules, including actin‐targeting natural products and anticancer drugs. Therefore, quantifying actin structural changes from high resolution fluorescence micrographs is necessary for further understanding actin cytoskeleton dynamics and phenotypic consequences of drug interactions on cells. We applied an artificial neural network algorithm, which used image intensity and anisotropy measurements, to quantitatively classify F‐actin subcellular features into actin along the edges of cells, actin at the protrusions of cells, internal fibers and punctate signals. The algorithm measured significant increase in F‐actin at cell edges with concomitant decrease in internal punctate actin in astrocytoma cells lacking functional neurofibromin and p53 when treated with three structurally‐distinct anticancer small molecules: OSW1, Schweinfurthin A (SA) and a synthetic marine compound 23'‐dehydroxycephalostatin 1. Distinctly different changes were measured in cells treated with the actin inhibitor cytochalasin B. These measurements support published reports that SA acts on F‐actin in NF1−/− neurofibromin deficient cancer cells through changes in Rho signaling. Quantitative pattern analysis of cells has wide applications for understanding mechanisms of small molecules, because many anti‐cancer drugs directly or indirectly target cytoskeletal proteins. Furthermore, quantitative information about the actin cytoskeleton may make it possible to further understand cell fate decisions using mathematically testable models. Published 2014 Wiley Periodicals Inc.